Physicochemical, physical characteristics and antioxidant activities of three edible red seaweeds (Kappaphycus alvarezii, Eucheuma spinosum and Eucheuma striatum) from Sabah, Malaysia - Farah Nurshahida, Mohd Subakir; Nazikussabah, Zaharudin; Subramaniam, Suganthi R.; W. I., Wan Faizal; Nurul Aini, Mohd Azman (IOP Publishing Ltd, 2020)
Kappaphycus alvarezii (KA), Eucheuma spinosum (ESp) and Eucheuma striatum (Est are tropical red seaweeds taken from Kunak, Sabah, contain essentials source of bioactive compounds to produce variety of functional foods. This study was intended to investigate the physicochemical, physical properties and antioxidant activities related to these edible seaweeds. Physicochemical properties value of swelling capacity (SWC) and oil retention capacity (ORC) in KA species showed the highest value (p<0.05) compared to ESp and ESt, and water retention capacity (WRC) in ESp species was significantly different than KA and ESt (p<0.05). As in physical properties, ESp exhibited higher in moisture content and opacity than KA and ESt. KA showed the highest water solubility (p<0.05) which associated to its carrageenan compound. The antioxidant activities; DPPH and TEAC assay with total phenolic content (TPC) of three seaweed species indicated that KA displayed the highest TPC (19.17±0.04 mg GAE/g DW) and the lowest radical scavenging activity in both TEAC and DPPH assays. Hence, the findings disclose the physical and physiochemical properties and antioxidant values of these seaweeds application as new information and potential antioxidant sources in foods manufacturing commodities.